Leaders’ Understanding of Evidence-Based Practices: A Survey of Police Chiefs and Probation/Parole Chiefs - Kim, Bitna (American journal of criminal justice, 2024)
Immense pressure is being put on criminal justice agencies to adopt and implement evidence-based practices (EBP). Empirical evidence highlights the need for leadership support to make agencies more evidence-based. The current study is an empirical examination of how criminal justice leaders understand EBP and its correlates or predictors in the domains of agency characteristics, individual characteristics, and openness to research partnerships. Data were collected through a statewide survey of police chiefs and chief probation/parole officers in Pennsylvania. Using a multinomial logistic regression model and a binary logistic regression model, correlates and predictors of familiarity and accuracy with EBP were identified. About 32% had never heard of EBP, 27% were familiar with it but did not define it correctly, and 41% held some knowledge of it. Results showed that EBP training may have introduced EBPs to leaders, but it failed to teach them what EBP actually is, and their lack of knowledge of EBP may be contributing to their lack of participation in research partnerships. By providing recommendations based on findings related to EBP training and research partnerships, the current research contributes to the ongoing discussion regarding challenges associated with EBP implementation and acceptance of EBPs among criminal justice practitioners.